Historian hajuista tuoksujen tulevaisuuteen pääkaupunkiseudun jätevedenpuhdistuksen keskeiset päätökset Espoon näkökulmasta - S. Juuti, Petri (Tampere University Press, 2017)
"From Stinky History to Fragrant Future. Waste water treatment of the metropolitan area - central decisions on the point of view of Espoo is written by Adjunct Professor, PhD Petri S Juuti. The book examines how water and waste water services started and developed in Espoo from the 1950s to the 2000s. Furthermore, it is discussed what are the challenges of the future looked from the point of view of the professionals of the water sector."